Cumulative rabbit anti-human thymocyte globulin dose to recipient weight during the peri-operative period is an independent risk factor for early postoperative urinary tract infection after kidney transplantation - Shujuan Li; Ziyu Wang; Zhen Dong; Yanwei Cao; Hongyang Wang (Renal Failure)
Anti-human thymocyte globulin-Fresenius (ATG-F) is frequently utilized to achieve successful induction for kidney transplantation recipients. This study aimed to examine the association between the ATG-F dose-to-recipient-weight ratio (ADR) and the risk of developing urinary tract infections (UTIs) following kidney transplantation. Data of kidney transplant recipients who underwent ATG-F-induction peri-operatively in a medical center were retrospectively collected, and the incidence of UTIs during the first postoperative year was also recorded. The risk of UTI associated with ADR was analyzed, and receiver operating characteristic curves were drawn to determine the optimal ADR, followed by Cox regression models. In total, 131 recipients were included, with an UTI incidence of 19.08% and a mean interval of 3.08 months. The optimal ADR was 6.34, involving 41 and 90 patients in the low ADR and high ADR groups, respectively. The UTI-free rate in the low ADR group was significantly higher than that in the high ADR group (p = 0.007). Cox regression analysis indicated that a high ADR independently increased the risk of UTI following kidney transplantation (hazard ratio: 5.306, 95% confidence interval: 1.243–22.660, p = 0.024). There was no significant difference in rejection rate between the high ADR and low ADR groups. In conclusion, a high ADR increased the incidence of early postoperative UTI among kidney transplant recipients.